EVALUASI KINERJA STRUKTUR GEDUNG BERTINGKAT DENGAN ANALISIS RIWAYAT WAKTU TERHADAP DRIFT DAN DISPLACEMENT MENGGUNAKAN SOFTWARE ETABS (STUDI KASUS : HOTEL DI DAERAH KARANGANYAR) - Firman Andriyanto; Agus Setiya Budi; Wibowo Wibowo (Program Studi Teknik Sipil FT UNS, 2014)
Indonesia lies between severally tektonik's plate universalizes, which is Australian Eurasian plate one moves to aim northern, moving Pacific plateto aim Eurasia's northwest and plate, so often experiences earthquake. Sighted by geological, Indonesian archipelago lies on appointment 2 mainearthquake bands, which is earthquake Sirkum Pacific and Alpide Transasiatic's earthquake band, in consequence Indonesia includes in ringband damp down Pacific (ring of fire). Ring damps down Pacific constitute world active mountain series causative Indonesian experience earthquakefrequency that adequately frequent. It bears out the importance for review strategical earthquake charges be in contemplation structure designin anticipation if happening earthquake. In common structure analysis to earthquake is divided as 2 kinds, which is static analysis and dynamicanalysis (respon spectrum analysis and time history analysis). This research has a purpose to know building structure performance bases drift anddisplacement. Observational method that is utilized is analisis dynamic time history by use of software ETABS. Buildings structure evaluationby give earthquake record note El Centro, Chi Chi Taiwan, Kobe Japan and Indonesian Sumatera. If building was given by charges El Centro'searthquake, Chi Chi Taiwan, Kobe Japan and Indonesian Sumatera is gotten safe to inspire angles nominal basic. Helper bounds performanceand ultimit's bounds performance that ineligible appropriate SNI 1726 2002 sections 8.1 and sections 8.2 is El Centro's earthquake record andIndonesia Sumatera. According to ATC-40, if building was given by charges El Centro's earthquake, Chi Chi Taiwan, Kobe Japan and IndonesianSumatera therefore building performance comes in category IO (Immediate Occupancy).